(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reading and Recalling skill provides support to prospective teachers with new learning ways and practices. The art of generative teaching is knowing how and when to facilitate the learner’s construction of relations among the parts of the text and their knowledge. The aim of the study is to find the impact of generative study strategies of the prospective teachers’ reading and recall of short stories. Experimental method was adopted in this study. The sample consists of 60 prospective teachers with both male and female of summarization group, question-generation group and control group in Thoothukudi area. Simple random sampling technique was used. R.K.Narayanan’s three short stories were selected as the material for the study. The statistical techniques used were mean, standard deviation, t-test and Pearson product moment correlation. The findings were: there was significant relationship between prospective teachers’ reading comprehension and recall test of the three groups. There was also positive correlation with respect to gender, locality, medium of instruction in school level and college level, speaking in English and reading English story books among the groups.